Facsimile Shaping of Subjective-Detrimental Demeanor Analogous to the Escalation of HIV/AIDS in Port, Harcourt, Nigeria - Akikibofori, Jacob Sunday (NIU Journal of Social Sciences; Vol 6 No 1 (2020): KIU Journal of Social Sciences, Vol. 6 No. 1, March 2020, 2020)
This article explores the state-of-the-art contention having to do with choosing spouse (positive (+) or negative (-) and being indiscriminately sexually active, in addition their trappings on the escalation of the HIV Virus and Aids infection. The emissary- established facsimile shaping is built to examine the fall out of these elements on the escalation of the disease amidst sexually- simmering, high-risk individual in Port Harcourt Nigeria. the outcome of the investigation conjecture that selecting a spouse (positive or negative), determination making usual procedure concerning if to truck with intercourse action hinged individual’s HIV condition, is a compelling blueprint in accommodating the disease when exercised frequently. The parallel of lewdness has brewed aftermath concerning the escalation of the virus. Keywords: Aftermath, lewdness, facsimile, escalation, high-risk, virus, disease, condition.